Comparison of the therapeutic effects of sildenafil citrate, heparin and neuropeptides in a rat model of acetic acid-induced gastric ulcer - Kalayci, Mehmet; Kocdor, Mehmet Ali; Kuloglu, Tuncay; Sahin, Ibrahim; Sarac, Mehmet; Aksoy, Aziz; Aydin, Suleyman (Pergamon-Elsevier Science Ltd, 2017)
Aims: The purpose of our investigative work has been to determine whether there can be therapeutic roles in the administration of sildenafil citrate, heparin and several neuropeptides on an animal model where gastric ulcers were induced with acetic acid, and to compare their efficacy. Materials and methods: The animals were divided into 13 groups, with 4 animals in each. Gastric ulcers was induced in the animals of 12 groups with one untreated group being left as the control (Group I - control; given normal saline (NS)). The other groups were: Group II (ulcer + NS); Group III (5 mg/kg sildenafil citrate, low dose); Group IV (10 mg/kg sildenafil citrate, high dose); Group V (0.6 mg/kg heparin, low dose); Group VI (6 mg/kg heparin, high dose); Group VII (20 nmol/kg des-acyl ghrelin); Group VIII (40 nmol/kg des-acyl ghrelin); Group IX (4 nmol/kg acyl ghrelin); Group X (8 nmol/kg acly ghrelin); Group XI (20 pmol/kg Nesfatin-1); Group XII (15 nmol/kg Obestatin) and Group XIII (5 nmol/kg Neuropeptide Y). Gastric neuropeptide expression was measured using an immunohistochemical method, and the amount in circulation was detected using ELISA. To compare with no treatment, the controls and other treatment groups, we recorded loss of the surface epithelium of the stomach, erosion, bleeding and inflammatory cell infiltration in the upper halves of the gastric glands. Key findings: The muscularis and the layers beneath it were, however, apparently normal. The gastric mucosa healed with little or no inflammation when sildenafil citrate, low dose heparin, ghrelin, NUCB2/Nesfatin-1, obestatin, Neuropeptide Y were administered. Significance: Overall the data indicate that low dose heparin, and especially sildenafil citrate and neuropeptides, can be used clinically as an alternative approach in the treatment of the gastric ulcer.
Keywords: Gastric ulcer; Sildenafil citrate; Heparin; Neuropeptide; Immunohistochemistry